Reversal of Tumor Immune Inhibition Using a Chimeric Cytokine Receptor - Leen, Ann M (Nature Publishing Group, 2014)
The success of adoptively transferred tumor-directed T cells requires them to survive and expand in vivo. Most tumors, however, employ immune evasion mechanisms, including the production of inhibitory cytokines that limit in vivo T-cell persistence and effector function. To protect tumor-directed T cells from such negative influences, we generated a chimeric cytokine receptor in which the interleukin (IL) 4 receptor exodomain was fused to the IL7 receptor endodomain. We thereby inverted the effects of tumor-derived IL4 so that the proliferation and activation of tumor directed cytotoxic T cells was enhanced rather than inhibited in the tumor microenvironment, resulting in superior antitumor activity. These transgenic T cells were only activated in the tumor environment since triggering required exposure to both tumor antigen (signal 1) and tumor-derived IL4 (signal 2). This selectivity supports future clinical adaptation.